Understanding the effect of host structure of nitrogen doped ultrananocrystalline diamond electrode on electrochemical carbon dioxide reduction. (February 2020) - Wanninayake, Namal; Ai, Qianxiang; Zhou, Ruixin; Hoque, Md Ariful; Herrell, Sidney; Guzman, Marcelo I.; Risko, Chad; Kim, Doo Young
Abstract: Despite recent literature reporting the remarkable electrochemical CO2 reduction reaction (CO2RR) performance of nitrogen-doped graphitic carbon materials ( sp 2 -carbon) and nitrogen-doped diamond materials ( sp 3 -carbon), no systematic studies have been conducted on the catalytic activities of hybrid carbon nanomaterials between diamond and graphitic extremes. In this study, nitrogen-doped ultra-nanocrystalline diamond thin films were prepared by a microwave-assisted chemical vapor deposition technique. The ratio of sp 2 -carbon phase to sp 3 -carbon phase was controlled by varying growth conditions. Our results confirm that nitrogen-doped sp 2 -carbon (graphitic) rich electrodes have better selectivity for the CO2RR products over the nitrogen-doped sp 3 -carbon rich electrodes, indicating that the host structure of nitrogen dopants is crucial for the catalytic activity. Nitrogen-doped sp 2 -carbon electrodes present Faradaic efficiency for CO production up to 82% with excellent activity and selectivity. The vital role of the host structure and the potential catalytic sites were detailed by density functional theory (DFT) calculations. Graphical abstract: Image 1